ON UPPER AND LOWER WEAKLY \(I\)-CONTINUOUS MULTIFUNCTIONS - Arivazhagi, C.; Rajesh, N. (Italian Journal of Pure and Applied Mathematics, 2016)
In this paper, we introduce and study a new generalization of \(I\)-continuous multifunctions called weakly \(I\)-continuous multifunctions in topological spaces.